2009
DOI: 10.1152/ajpcell.00240.2009
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine enhances heat shock protein 70 expression via increased hexosamine biosynthetic pathway activity

Abstract: Hamiel CR, Pinto S, Hau A, Wischmeyer PE. Glutamine enhances heat shock protein 70 expression via increased hexosamine biosynthetic pathway activity. Am J Physiol Cell Physiol 297: C1509 -C1519, 2009. First published September 23, 2009 doi:10.1152/ajpcell.00240.2009.-Glutamine (GLN) plays a key role in cellular protection following injury via enhancement of heat shock protein 70 (HSP70). The pathway by which GLN enhances HSP70 is unknown. GLN is a key substrate for the hexosamine biosynthetic pathway (HBP), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 30 publications
5
86
0
1
Order By: Relevance
“…1), it has been postulated that glutamine may work in an O-GlcNAc-dependent manner. In support of this hypothesis, in vivo treatment with glutamine has been shown to elevate OGlcNAc levels (Singleton and Wischmeyer 2008;Hamiel et al 2009). Moreover, the ability of glutamine to induce HSP70 is attenuated in cells in which O-GlcNAc levels have been lowered (Hamiel et al 2009).…”
Section: Heat Shock Protein Expressionmentioning
confidence: 92%
See 2 more Smart Citations
“…1), it has been postulated that glutamine may work in an O-GlcNAc-dependent manner. In support of this hypothesis, in vivo treatment with glutamine has been shown to elevate OGlcNAc levels (Singleton and Wischmeyer 2008;Hamiel et al 2009). Moreover, the ability of glutamine to induce HSP70 is attenuated in cells in which O-GlcNAc levels have been lowered (Hamiel et al 2009).…”
Section: Heat Shock Protein Expressionmentioning
confidence: 92%
“…In support of this hypothesis, in vivo treatment with glutamine has been shown to elevate OGlcNAc levels (Singleton and Wischmeyer 2008;Hamiel et al 2009). Moreover, the ability of glutamine to induce HSP70 is attenuated in cells in which O-GlcNAc levels have been lowered (Hamiel et al 2009). In heat-stressed cells and a septic mouse model, glutamine treatment appears to promote the nuclear accumulation of HSF-1 and Sp1 in an OGlcNAc-dependent manner (Singleton and Wischmeyer 2008;Hamiel et al 2009).…”
Section: Heat Shock Protein Expressionmentioning
confidence: 92%
See 1 more Smart Citation
“…20,21 The ability of cells to respond to and survive stressful conditions is known to be influenced by glucose and glutamine-dependent O-GlcNAcylation through the hexosamine biosynthetic pathway (HBP), in which both mentioned substrates are enzymatically converted to the high-energy metabolite UDP-N-acetylglucosamine (UDP-GlcNAc), which is then covalently attached to serine, threonine, or tyrosine residues of proteins under UDP release. [22][23][24][25] In contrast to other types of O-and N-linked glycosylation, O-GlcNAcylation is a primarily nuclear and cytosolic glycosylation with a single O-GlcNAc moiety and in contrast to more complex glycan structures, a dynamic process more akin to phosphorylation. 20 The enzymes O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA) keep the rates of glycosylation and deglycosylation in a dynamic equilibrium and ready to respond to environmental stimuli, such as the availability of glucose, combined with a hyperosmolar injurious stress.…”
mentioning
confidence: 99%
“…21 Hamiel et al 22 found that Gln metabolism enhances HSP70 expression by increasing the hexosamine biosynthetic pathway activity, with the O-glycosylation, nuclear translocation, and transcriptional activation of Sp1 and heat shock factor-1 (HSF1) being responsible. Zachara et al 23 reported that stress (including thermal stress) applied to cells rapidly increases the O-glycosylation of intracellular proteins, which is associated with increased HSP70 expression.…”
Section: Discussionmentioning
confidence: 99%